Pengaruh Pemberdayaan, Efikasi Diri dan Budaya Organisasi terhadap Kinerja Pegawai Dinas Perpustakaan Kota Sibolga - Leonard Harianto Marpaung; Elwadip Ardi Friska Hasibuan; Syarifullah S; Erika Sari Siregar (Universitas Islam Sumatera Utara, 2022)
Problem of this study what is influence of empowerment on performance. What is influence of self efficacy on performance. What is influence of organization culture on performance. What is influence empowerment, self efficacy and organization culture on performance. The purpose of this study to determine and analyze the effect of empowerment on performance. Determine and analyze the effect of self efficacy on performance. Determine and analyze the effect of organization culture on performance. Determine and analyze the effect of empowerment, self efficacy and organization culture on performance. Sample in the study is 34 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate empowerment variable has a positive and significant effect on performance. self efficacy variable has a positive and significant effect on performance. Organization culture variable has a positive and significant effect on performance. empowerment, self efficacy and organization culture variable has a positive and significant effect on performance